The 8th GOSPEL Workshop. Gas Sensors Based on Semiconducting Metal Oxides: Basic Understanding &Amp;amp; Application Fields 2019
DOI: 10.3390/proceedings2019014036
|View full text |Cite
|
Sign up to set email alerts
|

High Temperature Resistive Gas Sensors Based on ZnO/SiC Nanocomposites

Abstract: The work is aimed at creating ZnO/SiC composites for resistive type gas sensors towards maincomponents of exhaust gases [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…This discontinuity and roughness make the AAq thin film more favorable for humidity sensor. In our previous work on MO [27], the SEM micrographs were presented which revealed that roughness of the MO film leads to better humidity sensitivity of the sensor. Also, CoPc [29] and VOPc [10] morphological studies by using AFM analysis exhibited the same behavior, i.e., roughness was favorable for the humidity sensing of the sensor.…”
Section: Materials Characterizationmentioning
confidence: 98%
See 1 more Smart Citation
“…This discontinuity and roughness make the AAq thin film more favorable for humidity sensor. In our previous work on MO [27], the SEM micrographs were presented which revealed that roughness of the MO film leads to better humidity sensitivity of the sensor. Also, CoPc [29] and VOPc [10] morphological studies by using AFM analysis exhibited the same behavior, i.e., roughness was favorable for the humidity sensing of the sensor.…”
Section: Materials Characterizationmentioning
confidence: 98%
“…Due to low power consumption, capacitive-type humidity sensors are more popular [22] since low power sensors are very attractive to reduce the power consumption so that they can be powered by energy harvesting system [23][24][25]. In comparison with resistive-type sensors, capacitive-type sensors show better stability at higher humidity level and temperature [26][27][28][29]. Most sensors based on organic semiconductors are fabricated in either sandwich or surface type configurations with the former deemed reliable but suffer being easily damaged are susceptible to shortening problems [30].…”
Section: Introductionmentioning
confidence: 99%
“… Panels a–d of Figure present the O 1s spectra for 3C-SiC/NCO in 1:1, 1:1.5, and 1:2 weight ratios, respectively. Two of the same peaks around 530.1 and 532.3 eV are observed in these samples, which are respectively corresponding to the lattice oxygen and surface oxygen vacancy . Surface oxygen vacancy is formed after the formation of the heterostructure, which can facilitate ionic transport in the interface.…”
mentioning
confidence: 90%
“…Two of the same peaks around 530.1 and 532.3 eV are observed in these samples, which are respectively corresponding to the lattice oxygen and surface oxygen vacancy. 21 Surface oxygen vacancy is formed after the formation of the heterostructure, which can facilitate ionic transport in the interface. Besides, the peak around 536.2 eV was also detected, which can be ascribed to Na KLL Auger signal.…”
mentioning
confidence: 99%